2008
DOI: 10.1063/1.2905212
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the deformation of a ferrogel sphere in a homogeneous magnetic field

Abstract: A sphere of a ferrogel is exposed to a homogeneous magnetic field. In accordance to theoretical predictions, it gets elongated along the field lines. The time-dependence of the elastic shear modulus causes the elongation to increase with time analogously to mechanic creep experiments, and the rapid excitation causes the sphere to vibrate. Both phenomena can be well described by a damped harmonic oscillator model. By comparing the elongation along the field with the contraction perpendicular to it, we can calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 24 publications
4
53
0
Order By: Relevance
“…Provided that a firm coupling of the particles to the polymer network -either by chemical linkage or steric confinement -exists, a mechanical response of the composite can be stimulated by an external magnetic field [2][3][4][5]. As an example, when a ferrogel is exposed to a magnetic field gradient, the magnetophoretic force acting on the particles is transferred to the polymer network leading to a large and rapid deformation of the ferrogel body.…”
Section: Introductionmentioning
confidence: 98%
“…Provided that a firm coupling of the particles to the polymer network -either by chemical linkage or steric confinement -exists, a mechanical response of the composite can be stimulated by an external magnetic field [2][3][4][5]. As an example, when a ferrogel is exposed to a magnetic field gradient, the magnetophoretic force acting on the particles is transferred to the polymer network leading to a large and rapid deformation of the ferrogel body.…”
Section: Introductionmentioning
confidence: 98%
“…The surface effect has been studied extensively both theoretically [1], [9], [10], [11] and experimentally [12]. It was found that spheres of ferrogel can strain up to 2% when placed in a homogeneous magnetic field and form axisymmetrial non-spheroidal shapes with their axis aligned with the field direction.…”
Section: Introductionmentioning
confidence: 99%
“…[16]. The magnetisation of the spherical sample was then measured by means of a fluxmetric magnetometer (Lake shore, model 480) at θ = 20 C. Figure 2 shows this data.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…This is handy for many upcoming applications, such as soft actuators, magnetic valves, magnetoelastic mobile robots [8], artificial muscles [9] or magnetic controlled drug delivery [10][11][12][13]. Most of the applications are based on the continuous deformation of ferrogel bodies in gradient fields [14] or in homogeneous fields [15,16]. Another promising effect, which so far has not been exploited, is the drastic shape transition of ferrogels in the succession of the Rosensweig instability.…”
Section: Introductionmentioning
confidence: 99%